Peran Kepala Madrasah dalam Pengembangan Profesionalisme Guru Di MA Darul Falah Cukir Jombang - Nurul Indana; Al Qutbi Amin (At Tadbir: Islamic Education Management Journal, 2023)
The purpose of this study was to determine the strategies carried out by the madrasah head in developing teacher professionalism at MA Darul Falah Cukir Jombang, knowing the professionalism of teachers at MA Darul Falah Cukir Jombang, and the supporting and inhibiting factors for developing teacher professionalism at MA Darul Falah Cukir Jombang. To get answers to the above problems, the author conducted research with qualitative methods. Qualitative method is research that starts from a problem where the problem can develop and change during the field. After analyzing the data obtained, the results show that the strategies carried out by the madrasah head of MA Darul Falah Cukir Jombang in developing teacher professionalism are: First, finding out the shortcomings of teachers through supervision activities. Second, calling in and providing guidance. Third, include seminars such as MGMP and workshop. In implementing supervision, the principal of MA Darul Falah Cukir Jombang is assisted by waka-waka and also by other employees. The madrasah head will call teachers who are still declared lacking in something and provide direction to improve the teacher's shortcomings. With the support and motivation from the madrasah head, the teachers have broader experience and insight. There are 2 factors that inhibit the development of teacher professionalism in MA Darul Falah Cukir Jombang. First, the diversity of students at MA Darul Falah Cukir Jombang makes it difficult for teachers to provide understanding that can be digested easily by students. Second, the lack of funds for facilities and pre-facilities which results in the teaching and learning process being less effective.